2009
DOI: 10.1002/j.2334-5837.2009.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Agent‐Based Modeling the Emergent Behavior of A System‐of‐Systems

Abstract: Net‐Centric Operations (NCO) is operated on a System‐of‐Systems (SoS) communication environment. Emergent behavior is one of the five SoS characteristics. Layered SoS architectures start from the top SoS‐level containing emergent behavior. Conceptual agent‐based modeling was presented to simulate the four principles of emergence. The simulations covered the condition of emergence, non‐linear behavior and coupling relationship between agents. The four principles are interrelated. The emergent behavior has impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…(s1) [Teixeira et al 2020], (s2) [Binder et al 2019], (s3) [Manzano et al 2019], (s4) [Beery et al 2019], (s5) [Graciano Neto et al 2018b], (s6) [Zhang et al 2018], (s7) [Graciano Neto et al 2018a], (s8) [Zhuang et al 2018], (s9) [Esmaeilzadeh et al 2018], (s10) [Dahmann et al 2017], (s11) [Graciano Neto et al 2017], (s12) [Silva et al 2017], (s13) [Hachem et al 2016], (s14) [Oquendo et al 2016], (s15) [Li et al 2013], (s16) [Yousefi and Levis 2016], (s17) [Arnold et al 2016], (s18) [Spichkova et al 2015], (s19) [Li et al 2016b], (s20) [Wang et al 2015], (s21) [Cavalcante 2015], (s22) [Wätzoldt and Giese 2015], (s23) [Perišić et al 2015], (s24) [Hu et al 2014], (s25) [Hsu et al 2014], (s26) [Rieckmann et al 2013], (s27) [Ge et al 2013], (s28) [Li et al 2013], (s29) [Ludwig et al 2011], (s30) [Wang and Dagli 2011], (s31) [Xiong et al 2010], (s32) [Garcia and Tolk 2010], (s33) [Sindiy et al 2009], (s34) [Robbins 2009], (s35) [Rao et al 2008]. We answer the raised research questions, as follows.…”
Section: Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…(s1) [Teixeira et al 2020], (s2) [Binder et al 2019], (s3) [Manzano et al 2019], (s4) [Beery et al 2019], (s5) [Graciano Neto et al 2018b], (s6) [Zhang et al 2018], (s7) [Graciano Neto et al 2018a], (s8) [Zhuang et al 2018], (s9) [Esmaeilzadeh et al 2018], (s10) [Dahmann et al 2017], (s11) [Graciano Neto et al 2017], (s12) [Silva et al 2017], (s13) [Hachem et al 2016], (s14) [Oquendo et al 2016], (s15) [Li et al 2013], (s16) [Yousefi and Levis 2016], (s17) [Arnold et al 2016], (s18) [Spichkova et al 2015], (s19) [Li et al 2016b], (s20) [Wang et al 2015], (s21) [Cavalcante 2015], (s22) [Wätzoldt and Giese 2015], (s23) [Perišić et al 2015], (s24) [Hu et al 2014], (s25) [Hsu et al 2014], (s26) [Rieckmann et al 2013], (s27) [Ge et al 2013], (s28) [Li et al 2013], (s29) [Ludwig et al 2011], (s30) [Wang and Dagli 2011], (s31) [Xiong et al 2010], (s32) [Garcia and Tolk 2010], (s33) [Sindiy et al 2009], (s34) [Robbins 2009], (s35) [Rao et al 2008]. We answer the raised research questions, as follows.…”
Section: Reportingmentioning
confidence: 99%
“…RQ1 -What research treads can be observed over the years? Interestingly, even after the rise of automatic transformation approaches, it is still possible to identify studies that manually synthesize the architecture proposal into ExM [Beery et al 2019, Esmaeilzadeh et al 2018, Hsu et al 2014, Teixeira et al 2020, Wang et al 2015, Yousefi and Levis 2016. No convergence in the community towards a common technology or tool was observed.…”
Section: Reportingmentioning
confidence: 99%
“…The results of both scoring criteria were merged and all papers with an aggregated score of at least 6 were included in the literature list. Complementing this list with our previous two articles [ 19 , 20 ] and four manually added papers [ 64 , 65 , 66 , 67 ], resulted into a total of 46 papers [ 19 , 20 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ,…”
Section: Requirements For the Enterprise Architecturementioning
confidence: 99%
“…Nevertheless, a total of 26 ( ) papers concerned either an ongoing study or a complete study, which implies that there is some mature basis from whereon we can build further. Furthermore, it is interesting that several papers [ 19 , 20 , 77 , 78 , 79 , 86 , 93 , 95 , 96 ] use agent-based modeling techniques to support their work.…”
Section: Requirements For the Enterprise Architecturementioning
confidence: 99%
“…Moreover, the behavior of most systems designed and developed nowadays cannot always be directly evaluated based only on the behavior of the individual systems or subsystems. In this paper, we define complex systems as entities where interactions between the parts have a fundamental impact on the global behavior, and the effect of dependencies is difficult to ascertain by simple inspection during design (Mane et al 2011;Nai Fovino and Masera 2006;Hsu et al 2009). Throughout this paper, we will use the term systems to refer to this class of complex systems.…”
Section: Introductionmentioning
confidence: 99%